siberian-style conversion - Lidin, Konstantin (project baikal, 2018)
How everything is changing! What once was bird Now lies a page of words; Thought was once a simple bloom; on bull’s slow feet A march did poems beat. And what was me anew, perhaps, has flourished, And leaves the plant world nourished. N. Zabolotsky, Metamorphoses (Translated by Leo Shtutin) The meaning of the Latin word ’conversion’ is close to the Greek ‘metamorphosis’ but does not coincide with it. If metamorphosis is a change in the form, then conversion should be understood as a change in the meaning or idea. That is why conversion processes always have a tint of nostalgia for the lost ideas. Joseph Brodsky wrote: So few Greeks live in Leningrad today that we have razed a Greek church, to make space for a new concert hall, built in today’s grim and unhappy style. A Halt in the Desert (1966) However, we have tried to select some examples of optimistic, positive and life-affirming conversion. This section includes analytical materials on the conversion projects for industrial facilities in Irkutsk, Ulan-Ude and Barnaul.